2002
DOI: 10.1152/japplphysiol.01250.2001
|View full text |Cite
|
Sign up to set email alerts
|

Altered frequency responses of sympathetic nerve discharge bursts after IL-1β and mild hypothermia

Abstract: Although interleukin-1beta (IL-1beta) administration produces nonuniform changes in the level of sympathetic nerve discharge (SND), the effect of IL-1beta on the frequency-domain relationships between discharges in different sympathetic nerves is not known. Autospectral and coherence analyses were used to determine the effect of IL-1beta and mild hypothermia (60 min after IL-1beta, colonic temperature from 38 degrees C to 36 degrees C) on the relationships between renal-interscapular brown adipose tissue (IBAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Moreover, Niijima et al (210) reported that intravenous IL-1β increased adrenal and splenic SND, but produced only transient increases followed by sustained reductions in renal SND in urethane-anesthetized rats. Third, the frequency-domain coupling of SND bursts can be influenced by IL-1β alone and in response to combined IL-1β and mild hypothermia (150), suggesting an additional mechanism via which IL-1β can influence sympathetic nerve outflow. Fourth, IL-1β can modulate responses to other physiological interventions.…”
Section: Cytokines Immune System Mediators and Autonomic Nerve Respomentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Niijima et al (210) reported that intravenous IL-1β increased adrenal and splenic SND, but produced only transient increases followed by sustained reductions in renal SND in urethane-anesthetized rats. Third, the frequency-domain coupling of SND bursts can be influenced by IL-1β alone and in response to combined IL-1β and mild hypothermia (150), suggesting an additional mechanism via which IL-1β can influence sympathetic nerve outflow. Fourth, IL-1β can modulate responses to other physiological interventions.…”
Section: Cytokines Immune System Mediators and Autonomic Nerve Respomentioning
confidence: 99%
“…However, recent lines of inquiry have expanded the functional repertoire of the ANS by establishing an essential role for this system in regulating, integrating, and orchestrating processes between diverse physiological systems (49, 51, 71, 96, 112). Specifically, the results of many studies (71, 96, 97, 120, 121, 134, 135, 136, 150, 152, 181, 200, 256, 281, 296, 297, 298) have established a critical role for the ANS in mediating interactions between the nervous and immune systems, two important adaptive systems that were originally considered to function independently of each other. The physiology of ANS function and regulation involves numerous complex, dynamic, and integrated steps (e.g., neural outflow, transmitter synthesis, release and degradation, ganglionic regulation, receptor-mediated effects), many of which are likely involved in mediating neural-immune interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggest a relationship between activation of IL-1R and autonomic nervous system activity (see Graphical Abstract). Intravenous infusion of IL-1β in conscious rats 20 increased renal nerve activity and arterial pressure and spinal cord transection at C1 before infusion abolished sympathoexcitation, 21 suggesting a peripheral location of action involving activation of afferent pathways that modulate sympathetic activity.…”
Section: Potential Mechanisms Mediating the Interaction Of The Il-1r ...mentioning
confidence: 99%
“…Studies in experimental rats have shaped the contemporary understanding of central mechanisms regulating basal SND and the role of central neural circuits in mediating changes in SND responses to acute stress. For example, it is well-established that central sympathetic neural circuits in experimental rats are capable of producing heterogeneous SND response profiles to numerous interventions, including directionally opposite changes in the level of activity in sympathetic nerves innervating different targets and selectivity in the frequency-domain characteristics of discharge bursts in different sympathetic nerves (Kenney, 1994; Kenney et al, 2002; Kenney et al, 1999; Morrison, 2001; Ramchandra et al, 2006; Weiss et al, 1996). Moreover, it is well-recognized that multiple levels of the neuraxis contribute to regulation of efferent SND and that various pathophysiological conditions can alter the central regulation of SND in experimental animals (Dampney, 1994; Dampney et al, 2003; Guyenet, 2006; Loewy, 1990; Strack et al, 1989; Sun, 1995).…”
Section: Translational Physiology and Snd Recordingsmentioning
confidence: 99%